Carcinoma of accessory breast: an incidental finding - Obituyi, Hameed A.; Kehinde, Sunday O.; Fawehinmi, Folayemi; Gbajumo, Fadilat M.; Okogu, Stephen I.; Olajide, Folafunmi A.; Adeogun, Adebisi O. (International Surgery Journal, 2025)
Accessory breast carcinoma (ABT) is a rare disease, it accounts for less than 1% of breast cancers. ABT is often under diagnosed, therefore, it should be considered for all lumps presenting along the milk line (from axilla to groin). Reported cases show the most common area for accessory breast cancer to be the axilla. In this report, we report a 50-year- old woman with invasive ductal carcinoma of the accessory breast in her right axilla with metastasis to the axillary lymph node. She is currently undergoing chemotherapy as we write this article. The diagnosis of ABT is often delayed due to the frequent absence of an accessory areola or nipple, coupled with a lack of awareness among physicians and patients regarding these seemingly harmless-looking masses. Consequently, it is essential to thoroughly examine any mass along the mammary line and promptly evaluate suspicious lesions.